Engineered living materials for the conversion of a low-cost food-grade precursor to a high-value flavonoid - Riedel, Florian; Bartolomé, Maria Puertas; Enrico, Lara Luana Teruel; Fink-Straube, Claudia; Duong, Cao Nguyen; Gherlone, Fabio; Huang, Ying; Valiante, Vito; Del Campo, Aránzazu; Sankaran, Shrikrishnan (Frontiers in Bioengineering and Biotechnology, 2023)
Microbial biofactories allow the upscaled production of high-value compounds in biotechnological processes. This is particularly advantageous for compounds like flavonoids that promote better health through their antioxidant, antibacterial, anticancer and other beneficial effects but are only produced in small quantities in their natural plant-based hosts. Bacteria like E. coli have been genetically modified with enzyme cascades to produce flavonoids like naringenin and pinocembrin from coumaric or cinnamic acid. Despite advancements in yield optimization, the production of these compounds still involves high costs associated with their biosynthesis, purification, storage and transport. An alternative production strategy could involve the direct delivery of the microbial biofactories to the body. In such a strategy, ensuring biocontainment of the engineered microbes in the body and controlling production rates are major challenges. In this study, these two aspects are addressed by developing engineered living materials (ELMs) consisting of probiotic microbial biofactories encapsulated in biocompatible hydrogels. Engineered probiotic E. coli Nissle 1917 able to efficiently convert cinnamic acid into pinocembrin were encapsulated in poly(vinyl alcohol)-based hydrogels. The biofactories are contained in the hydrogels for a month and remain metabolically active during this time. Control over production levels is achieved by the containment inside the material, which regulates bacteria growth, and by the amount of cinnamic acid in the medium.